Time-resolved 3-dimensional magnetic resonance phase contrast imaging (4D Flow MRI) reveals altered blood flow patterns in the ascending aorta of patients with valve-sparing aortic root replacement - Oechtering, Thekla H.; Sieren, Malte M.; Hunold, Peter; Hennemuth, Anja; Huellebrand, Markus; Scharfschwerdt, Michael; Richardt, Doreen; Sievers, Hans-Hinrich; Barkhausen, Jörg; Frydrychowicz, Alex (The Journal of thoracic and cardiovascular surgery, 2020)
The aim of this study was to compare aortic flow patterns in patients after David valve-sparing aortic root replacement with physiologically shaped sinus prostheses or conventional tube grafts in healthy volunteers. Twelve patients with sinus prostheses (55 ± 15 years), 6 patients with tube grafts (58 ± 12 years), 12 age-matched, healthy volunteers (55 ± 6 years), and 6 young, healthy volunteers (25 ± 3 years) were examined with time-resolved 3-dimensional magnetic resonance phase contrast imaging (4D Flow MRI). Primary and secondary helical, as well as vortical flow patterns, were evaluated. Aortic arch anatomy as a flow influencing factor was determined. Compared with volunteers, both sinus prostheses and tube grafts developed more than 4 times as many secondary flow patterns in the ascending aorta (sinus prostheses n = 1.6 ± 0.8; tube grafts n = 1.3 ± 0.6; age-matched, healthy volunteers n = 0.3 ± 0.5; young, healthy volunteers n = 0; P ≤ .012) associated with a kinking of the prosthesis itself or at its distal anastomosis. As opposed to round aortic arches in volunteers (n = 16/18), cubic or gothic-shaped arches predominated in patients (n = 16/18, P < .001). In all but 3 volunteers, 2 counter-rotating helices were confirmed in the ascending aorta and were defined as a primary flow pattern. This primary flow pattern did not develop in patients who underwent valve-sparing aortic root replacement. In patients after valve-sparing aortic root replacement, there was an increased number of secondary flow patterns in the ascending aorta. This seems to be related to surgically altered aortic geometry with kinking. Because flow alterations are known to affect wall shear stress, there seems to be an increased risk for vessel wall remodeling. Compared with previous 4D Flow MRI studies, primary flow patterns in the ascending aorta in healthy subjects were confirmed to be more complex. This underlines the importance of thorough examination of 4D Flow MRI data.